A Variant in Genes of the NPY System as Modifier Factor of Machado-Joseph Disease in the Chinese Population - Ding, Dongxue; Chen, Zhao; Wang, Chunrong; Tang, Xiang; Zhang, Lulu; Fang, Qi; Qiu, Rong; Jiang, Hong (Frontiers in Aging Neuroscience, 2022)
Recently, NPY overexpression has been proposed to alleviate motor deficits and neuropathy in Machado-Joseph disease (MJD) mouse models, indicating its neuroprotective role in the pathogenesis of MJD. We aimed to evaluate the association between SNPs in NPY and its receptors and the susceptibility of MJD in the Chinese population. Moreover, we investigated whether these SNPs modulate the age at onset (AO) of MJD. In total, 527 MJD patients and 487 healthy controls were enrolled in the study, and four specific selected SNPs (rs16139, rs3037354, rs2234759, and rs11100494) in NPY and its receptor genes were genotyped. In this study, the genotypic frequency using the dominant model and the allelic distribution of rs11100494 in NPY5R revealed a significant difference between the MJD and control group during the first-stage analysis (p=0.048 and p=0.024, respectively). After we expanded the sample size, significant differences were observed between the two groups using the dominant model in genotypic and allelic distribution (p=0.034, p=0.046, and p=0.016, respectively). No significant differences in genotypic and allelic distribution were found between the MJD and control groups for the other three SNPs. All selected SNPs had no significant effect on the AO of MJD. The association of rs11100494 in the NPY5R gene and susceptibility of MJD suggested that the NPY system might be implicated in the pathogenesis of MJD. Our study demonstrated the existence of other genetic modifiers in MJD, along with CAG expansion and known genetic modifier factors, which might lead to a better understanding of MJD pathogenesis.